Risk Assessment and Mitigation Strategy of Large-Scale Solar Photovoltaic Systems in Pakistan - Inayat, Syeda Misbah; Zaidi, Syed Muhammad Rafay; Ahmed, Husnain; Ahmed, Danial; Azam, Mehreen Kausar; Arfeen, Zeeshan Ahmad (International Journal of Industrial Engineering and Management, 2023)
Solar photovoltaic (PV) systems and their installation are essential to determine a general practice for specialized risk assessment, which reduces the danger linked and the solutions to avoid those hazards, which call mitigation strategies. This paper aims to present the risk assessment and mitigation strategies for large-scale Solar PV systems in developing countries. To achieve this, complaints-related data has been collected from well-known companies providing Solar PV to industrial and residential consumers. This paper presents insights on the repetitive complaints, potential risks identified, and their severity along with probability. Further, risk mitigation strategies to resolve these complaints timely and significantly are listed by industry experts. Overall, the study briefed each risk, its detail, and classified the complaints in three different companies. Article history: Received (December 21, 2022); Revised (March 28, 2023); Accepted (April 7, 2023); Published online (April 18, 2023)